The role of attachment in the relationship between perceived parenting dimensions and bullying among preadolescents - Carter, Mariska (University of the Free State, 2017)
Bullying is the intentional and repetitive use of aggression against targets who cannot easily defend themselves. Bullying may be physical, verbal, or social-relational, or occur in the cyber context. Involvement in bullying is a matter of concern, as it may have negative implications for functioning of perpetrators and victims on individual and contextual levels. Risk factors that consistently correlate with bullying are parenting behaviour and the parent-child attachment relationship. There is limited research investigating the interaction between these constructs in the emergence of behaviour that constitute bullying. Thus, the study had three main objectives, namely (a) to determine whether significant relationships exist between perceived parenting dimensions (acceptance, firm control, and psychological control) and different types of bullying perpetration and victimisation (physical, verbal, social-relational, and in cyberspace); (b) to determine whether these relationships are mediated or moderated by parent-child attachment; and (c) to examine whether there are any significant gender and ethnic differences in different types of bullying perpetration and victimisation. A total of 1078 white Afrikaans- and black Southern Sotho-speaking preadolescents in Grades 5 and 6 from twenty-four schools across the Free State participated in the investigation. A quantitative, non-experimental type of study was conducted, utilising correlational and criterion group research designs. Data were collected during the second and third school terms by administrating measures of bullying, parenting dimensions, and parent-child attachment. Correlational analyses, hierarchical regression analyses, multiple regression analyses, moderated hierarchical multiple regression analyses, models of multivariate analysis of variance (MANOVAs), and analyses of variance (ANOVAs) were used to analyse the data. The findings suggest that although parenting dimensions significantly correlated with most types of bullying, they explained only a small proportion of the variance. In each case, perceived parental psychological control accounted for the major part of this variance. However, the corresponding effect sizes were found to be small. While attachment mediated most of the relationships between perceived parental acceptance and bullying, it mediated only the associations between firm control and physical and verbal bullying perpetration. Attachment and perceived parental acceptance interacted to influence verbal bullying perpetration. However, regardless of the levels of perceived parental acceptance, preadolescents with a lower quality of parent-child attachment were involved more frequently in verbal bullying perpetration. Attachment neither mediated nor moderated the relationships between perceived parental psychological control and bullying. While no meaningful gender differences were obtained, black Southern Sotho-speaking preadolescents were more involved in physical and verbal bullying perpetration and victimisation compared to white Afrikaans-speaking preadolescents. The results are discussed within a developmental psychopathology framework. Several practical applications of the findings, strengths, and limitations of the study, and areas for future research are highlighted.
Thesis (Ph.D. (Psychology))--University of the Free State, 2017
Keywords: Bullying; Victimisation; Parenting; Attachment; Preadolescence; Gender; Ethnicity; Mediator; Moderator